Lipid metabolites and nitric oxide production in the cerebrospinal fluid and plasma of dogs with meningoencephalitis of unknown origin and idiopathic epilepsy: a pilot study - Yonezawa, Tomohiro; Takenouchi, Shinya; Motegi, Tomoki; Miyazaki, Michiyo; Nagata, Nanae; Kobayashi, Koji; Yamada, Masaki; Murata, Takahisa (Frontiers in Veterinary Science, 2024)
Introduction: Idiopathic epilepsy (IE) and meningoencephalomyelitis of unknown origin (MUO) are common causes of brain diseases leading to seizures in dogs. In this study, the concentrations of 196 lipid metabolites and nitrogen oxide (NO) production in the cerebrospinal fluid (CSF) and plasma of dogs with MUO or IE were measured using a LC-MS/MS and a NOx analyzer, respectively. Methods: Nine clinically healthy dogs and 11 and 12 dogs with IE and MUO, respectively, were included in the study.Results: Lipid analysis revealed variations in the levels of four and six lipid metabolites in CSF and plasma, respectively, between the groups. The levels of 6-keto-prostaglandin (PG) F1α (PGF1α), 20carboxy arachidonic acid (20-carboxy-AA), 9-hydroxyoctadecadienoic acid, and lyso-plateletactivating factor were high in the CSF of dogs with MUO. In addition, the plasma levels of 11,12dihydroxyeicosatrienoic acid, 20-carboxy-AA, and oleoylethanolamide were high in dogs with IE, and those of PGF1α were high in dogs with MUO. NO production levels were high in CSF but not in plasma in dogs with MUO or IE.Discussion: It remains unknown whether these changes represent the cause or effect of diseases of the central nervous system; however, lipid metabolites and NO production in CSF and plasma may be used as diagnostic biomarkers and could be exploited for treating idiopathic or inflammatory epilepsy in dogs.